Defining good governance - Dey, Bata K. (1998)
Highlighting perceptual variations arising out of typology of governmental systems and connotations of its quality, the author defines the concept of good governance. He discusses with an illustrative survey what was perceived as good governance in the past in India by Kautilya, during Mughal and British rules, and post-independent Indian administration. While discussing present agenda of good governance, he highlights related constitutional provisions and goals of developments. He then gives his reflections on the present scenario of administration in India, identifying some major factors affecting the existing degeneration and contribution thereto by all the three wings - legislative, executive and judiciary. To remedy, the author discusses devising of a comprehensive strategy as envisaged under NEP and by the Fifth Pay Commission. He then gives a critical evaluation on the strategy of correctives. - Reproduced
Keywords: Public administration; Good governance